Design and implementation of advanced control laws for constrained robots - Yi, Ke. (2009)
Robots are playing very important roles in many manufacturing industries. Tasks such as assembly, grinding, and many other important jobs are performed through interactions between the robots and their environments. Hence, the motions of the robots are often constrained by the working environments. This thesis addresses the problem of controlling robots whose motions are constrained by the environments.